Neutrophil Extracellular Traps and Its Correlation with Several Pathological Conditions: Prosperities and Deleterious Implications - Phey Liana; Krisna Murti; Zen Hafy; Iche Andriyani Liberty; Tungki Pratama Umar (Cell and BioPharmaceutical Institute, 2022)
Neutrophil extracellular traps (NETs) are immune components found in a variety of pathological states. It has been shown to have either beneficial or harmful implications, depending on how it is controlled and has been particularly observed in three major scenarios: infection, autoimmune disease, and cancer. In this article, we compiled some of the roles of NETs in pathological conditions, as well as the benefits of targeting them for improved patient outcomes. The role of NETs were primarily positive in infectious disease, whether caused by bacteria, virus, or fungal infection. In non-infectious inflammatory scenarios, on the other hand, it's the complete opposite, with the effects being mainly deleterious and even worse than the original disease states. Targeting NETs directly or indirectly may help to prevent complications and improve patient outcomes. A plethora of compounds, including immunomodulators, anti-thrombosis, nicotinamide adenine dinucleotide phosphate (NADPH)/reactive oxygen species (ROS) inhibitors, nuclease, and other compounds, may be used to accomplish the therapeutic goals.Keywords: autoimmune disease, cancer, DNase, infection, neutrophil extracellular traps